PENGARUH TRANSFORMASI DIGITAL TERHADAP PRAKTIK AKUNTANSI MANAJEMEN DI ERA INDUSTRI 4.0 - Yuliati, Ni Nyoman (Jurnal Aplikasi Perpajakan, 2025)
This study aims to analyze the influence of digital transformation on the effectiveness of management accounting practices and to identify the digital technology components that contribute most to accounting-based managerial decision-making. The research was conducted on MSMEs in West Lombok Regency that have begun to implement digital applications in financial management. The approach used is quantitative with a causal associative research type. A sample of 100 respondents was selected using a purposive sampling technique. Data was collected using a Likert scale-based questionnaire and analyzed with multiple linear regression using SPSS version 26. The research results indicate that digital transformation, consisting of technology adoption and organizational readiness, significantly influences the effectiveness of management accounting practices both partially and simultaneously (p < 0.05). The organizational readiness component is the dominant factor with a beta coefficient of 0.694. This indicates that the successful implementation of management accounting digitalization in MSMEs depends not only on the availability of technology,- but also on the internal readiness of the organization.